PENGARUH BEBAN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN DIVISI LOGISTIK PT. POS INDONESIA KCU SURABAYA - Ivan Junian; Bowo Santoso; Mentari Dewanti (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to analyze the effect of workload and work stress on employee performance in the logistics division of PT Pos Indonesia KCU Surabaya. The observed phenomenon indicates a decline in employee performance over the past three years, which is suspected to be caused by high workload and work stress. This research employs a quantitative approach using a survey method by distributing questionnaires to all 45 employees in the logistics division through a saturated sampling technique. The collected data were analyzed using the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS). The results show that workload and work stress have a negative and significant effect on employee performance. This means that the higher the workload and work stress experienced, the lower the level of performance produced. These findings emphasize the importance of proportional workload management and effective work stress control to maintain motivation, productivity, and the sustainable achievement of employee performance targets.